A Design of Mobile Application for Ultrasound Bladder Monitoring System Based on Usability Engineering. Issue 1 (September 2020) - Park, Sangeun; Oh, Hyungyeong; choi, Jeonguk; Jang, Wonseuk
Patients with voiding dysfunction need continuous treatments as well as bladder ultrasonography, surgical procedures and medication. Ultrasound bladder monitoring healthcare system can help non-invasive treatment as a bladder training. This system uses wearable patch sensor so that patients can monitor their bladder volume as an indicator of voiding and be recommended voiding at a proper time. In this study, the mobile application for the system is designed and evaluated based on optimized clinical workflow and safety. This study included the design of clinical application models for users and the development of user interface complying with usability engineering process.